Palliative Care in Rural Aboriginal Communities: Conversations Around Experiences and Needs. Issue 6 (December 2021) - Spelten, Evelien R.; MacDermott, Sean; Morgan, Susan; Mitchell, Lynne; van Vuuren, Julia
Abstract : The aim of this study was to investigate the experiences and needs of Aboriginal community members with regard to rural community-based palliative care. Conversations with Aboriginal Elders were conducted. (In this Aboriginal community, Elders was not confined to older age. It referred to community leaders and includes [younger] emerging leaders.) The results were analyzed using descriptive analysis. Our study showed that there was a general lack of understanding of palliative care as distinct from curative care and limited awareness of services available. There was a strong need for clear information and on-call and practical support. Some concerns were expressed regarding limited awareness among health care providers of specific cultural needs. However, the home-based nature of palliative care was not, in itself, perceived as a barrier, provided that appropriate respect was displayed. We concluded that the current lack of understanding and awareness of services still impedes access to, and utilization of, care. More attention is needed for specific cultural needs. Adoption of a cultural humility approach for the promotion and delivery of palliative care seems to best fit the expressed needs and experiences of the participants.